Molybdenum oxide thin films grown on flexible ITO-coated PET substrates - Marciel, Alice (2021)
Molybdenum oxide thin films were deposited on stiff and flexible substrates by reactive DC magnetron sputtering. Two sets of samples were prepared. The first with different O2/Ar flow rate ratios and the second, fixing the oxygen content, with different time of deposition. As the O2/Ar flow rate ratio varies from 0 up to 0.56, a threshold was found, ranging from crystalline to amorphous nature, and from a nontransparent appearance with metallic-like electrical conductivity to transparent and dielectric behaviour. From the second set, all transparent, the MoOx films present a compact/dense and featureless morphology with thickness from 190 up to 910 nm, depending on the time of deposition. Their structure was corroborated by XPS and Rutherford Backscattering Spectrometry (RBS) and density measurements were performed by RBS and X-ray reflectivity (XRR), revealing a value of 2.4 g/cm3. The surface roughness is in the order of a few nanometers and the maxima optical transmission, in the visible range, is around 89%. Electrochemical cyclic voltammograms showed noticeable color reversibility and reproducibility on the flexible substrates opening new framework possibilities for new electrochomic devices.